PANDANGAN ORANG TUA TERHADAP PENDIDIKAN ANAK DI TEMPAT PEMBUANGAN AKHIR (TPA) SUMOMPO KECAMATAN TUMINTING KOTA MANADO - Sanjang, Greyne Veronica (Universitas Sam Ratulangi, 2014)
Education generally have a sense the processes of life by the individuals in developing them selves in order to livelife and were continuing. So as to be a who aretrained is very important. Education the first time we got at in the family, vicinity of the school and the community. Parents are implementing education, that his family was very tight loose and flexible, or had a flexible is different for a person’s own children. In everyday life that their parents is expected to follow him there’s free to leave any time to act foolishly. Educate parents have children in different ways. The family scavengers can bedescribed that most families scavengers had a temperament that hard work in accordance with the condition of the atmosphere, besides a lack of communication between the family because oftheir time more used to collect garbage, seen from social life of hard and lackof knowledge about religion that they are less useful things to use the time, this will impact on the economy of the results of those who hope his work. Parent’s views against child education gives direct impacts on the lives of child social. Children can adaptto around intercommunication on community school around and relies heavily on education pattern parents who applied to the child itself. Keywords:education, parent,scavenger